Absence of molecular evidence of Leptospira spp. in urine samples collected from rodents captured in Yucatán, México - Torres-Castro, Marco A.; Cruz-Camargo, Bayron E.; Medina-Pinto, Rodrigo; Moguel-Lehmer, Carlos; Arcila-Fuentes, William; Medina, Rolando; Ortiz-Esquivel, José; López-Ávila, Armando; Noh-Pech, Henry R.; Panti-May, Jesús A.; Rodríguez-Vivas, Roger I.; Puerto, Fernando I. (Austral Journal of Veterinary Sciences, 2017)
Leptospira spp. is a spirochete bacteria, causal agent of leptospirosis, zoonotic disease endemic in México that represents a serious public health and veterinary problem. Rodents are recognised as the most important reservoirs of this bacteria, which is transmitted mainly through direct or indirect contact with the Leptospira spp. excreted in the urine of infected individuals. The aim of this study was to evaluate the circulation of Leptospira spp. in urine samples of wild and synanthropic rodents from Yucatán, México. Eighty-four rodents were captured in the community of Cenotillo, Yucatán. Twenty-six urine samples were collected from the bladder and were used in the total DNA extraction. The identification of Leptospira spp. was intended through the polymerase chain reaction test in its endpoint variant. No evidence of Leptospira spp. was found in the urine samples. It is necessary to use other tissues for the identification of Leptospira spp., before concluding that the rodents used in the present study are not reservoirs of this bacteria.